Azotobacter and Pseudomonas Population in Rhizosphere and Yield of Choy Sum following Chemical Fertilizer and Biofertilizer application - Reginawanti Hindersah; Adita Rizky Syntianis; Ade Setiawan; Rina Devnita; Nursuhud Nursuhud (Faculty of Agriculture, Pattimura University, 2023)
Inoculation of beneficial microbes is a way to improve the population of rhizobacteria that has a role in nutrient cycle and hence reduce the level of chemical fertilizer. A pot experiment was performed to evaluate the effect of and consortia biofertilizer combined with various dose of NPK compound fertilizer on the population of nitrogen-fixing Azotobacter sp. and phosphate solubilizing Pseudomonas sp. in rhizosphere and yield of choy sum (Brassica juncea L.). The experimental was setup in completely randomized block design consisted of ten combinations of various biofertilizer and inorganic fertilizer dose; and three replications. The results showed that Biofertilizer inoculation with or without chemical fertilizer did not improve the population of Azotobacter and Pseudomonas in the rhizosphere but increase the shoot weight of choy sum. Higher shoot weight was showed by crops with ¾ dose of NPK combined with recommended or reduced dose of fertilizer; and recommended dose of NPK and biofertilizer. This experiment verified that the used of consortia biofertilizer composed of Nitrogen-fixing bacteria and phosphate-solubilizing microbes reduced 50-75% dose of NPK.